Depth-dependent parental effects create invisible barriers to coral dispersal - Tom Shlesinger; Yossi Loya (Communications Biology, 2021)
Tom Shlesinger and Yossi Loya use ex-situ and in-situ experiments with coral larvae of three brooding species from contrasting shallow- and deep-water habitats and show that larvae originating from deep-water corals have narrower tolerances and higher habitat-specificity in simulated parental-habitat conditions. They also show that survival of juvenile corals experimentally translocated to the sea was significantly lower when not at parental depths. Together these results demonstrate that local adaptations and parental effects interact with larval selectivity and phenotype-environment mismatches to create semipermeable barriers to coral dispersal and connectivity.